Are Controls the Answer? - Houthakker, Hendrik S. (The Review of Economics and Statistics, 1972)
W E shall not know for many months if AVIV the introduction of direct controls over wages and prices in late 1971 was followed by a significant slowdown in the trend of price and wage increases. Even if inflation will moderate somewhat, as is likely, economists will still be debating for years whether this can be attributed to the controls or whether it is simply the delayed result of considerable slack in the economy. But whatever the outcome of this future academic debate, some form of direct control is likely to be with us for some time. The establishment of direct controls on August 15, 1971 was popular among the public at large and subsequent opinion polls indicate that this program, despite its uncertain performance to date, has not become a political liability. The controls are only likely to be abandoned if they seriously hurt some important pressure group without visible offsetting benefits elsewhere, but this has not happened so far. Although some discontent among West Coast longshoremen gave most of the labor representatives on the Pay Board a pretext for walking out, most union members, and even the departed leaders themselves, are apparently quite willing to live with continued controls. The Price Commission has so far managed to avoid widespread criticism, except on the issue of food prices over which the Commission has only limited jurisdiction. Aside from public reaction, another reason for thinking that controls will not disappear soon is that inflationary pressures are likely to become more intense as the economy comes closer to capacity operation. If there is a case for controls when unemployment is around 6 per cent, it will be even stronger if unemployment drops to a more sustainable level. Unlike the control programs imposed in wartime, the present program has no natural termination point. The view that the present controls will be effective mainly by bringing about a reversal in inflationary psychology is not likely to be substantiated unless inflation can be curtailed much more drastically than official pronouncements suggest. A reduction in the inflation rate from 4 per cent to 3 per cent, while welcome, will scarcely allay widespread apprehension about large budget deficits and rapid monetary expansion. In fact, the belief that sheer psychology, as opposed to expectations based on experience, plays an important role in the inflationary process does not appear to be supported by any evidence. Unless real output can be made to grow at a much higher rate than has so far been achieved, the rapid growth in the money supply combined with the usual lags virtually guarantees the preservation of inflationary pressures well into 1973, if not longer.1 A recent Brookings study (Schultze et al. 1972, especially chapter 13) suggests that the Federal budget will not be a restraining influence either. If this prognosis for controls is correct, the question is what they will actually achieve. Even if attained, the modest reduction in the inflation rate officially set as a goal provides only weak justification for this drastic departure from our generally successful economic traditions. There is some indication that the Pay Board and Price Commission will serve less as a means of curtailing inflation than as watchdogs over big business and big labor. The three-tier classification of business firms by the Price Commission is one indication in this direction, and it has been further reinforced by the recent exemption of most small enterprices from price and wage controls. The Pay Board and the Construction Industry Stabilization Committee already spend most, if not all, of their time on organized labor. There is indeed a case for better supervision of the labor unions. In the last few years we